Legal Analysis: Settlement of Disputes Between Company Shareholders Through Arbitration - Siti Nurjannah Lase; Zahara Ananda; Salwa Khairina Azzahra; Shafa Zhafira Khalid; Gilang Ade Prabowo (ISNU Nine-Star Multidisciplinary Journal, 2025)
Disputes between shareholders are a common challenge in corporate practice and have the potential to cause instability within a company's internal structure. The open and time-consuming nature of litigation in court often deviates from business needs, which prioritize efficiency and confidentiality. Therefore, arbitration is seen as an alternative dispute resolution method that is more adaptable to the dynamics of the business world. This article examines the legal mechanism for resolving disputes between shareholders through arbitration, focusing on an analysis of the national legal framework, particularly Law Number 40 of 2007 concerning Limited Liability Companies and Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. The approach used is normative juridical, supported by literature review and jurisprudential analysis. The results of the study indicate that the existence of an arbitration clause in the articles of association or agreement between shareholders is a fundamental element in transferring jurisdiction from the courts to arbitration institutions. However, challenges remain in harmonizing norms and implementing consistent arbitration practices. Therefore, there is a need for strengthening regulations and legal education for stakeholders so that dispute resolution through arbitration can run optimally and provide legal certainty.